Profile of student's algebraic thinking in solving mathematics problems reviewing from adversity quotient - Ratna Sukmaningrum; Ika Kurniasari (Jurnal Pijar Mipa, 2022)
One way to solve problems in mathematics is to think algebraically. Algebraic thinking is thinking using generalization abilities, transformational abilities, and global meta-level abilities to solve problems. A person's ability to overcome and solve problems is called Adversity Quotient (AQ). There are three categories in Adversity Quotient (AQ): climber, camper, and a quitter. This study aimed to describe the profile of students' algebraic thinking in solving mathematical problems in terms of Adversity Quotient. This research is qualitative research with the subjects of this research are three grade IX junior high school students with different AQ categories. The instruments in this study were Adversity Response Profile (ARP) questionnaires, Problem Solving Tests (TPM), and interview guidelines. The qualitative data analysis technique follows the Miles and Huberman concept, which consists of three stages: data reduction stage, data presentation, and conclusion drawing. This study indicates that climber students perform all stages in solving problems and fulfill all indicators of algebraic thinking. Camper students did not carry out the re-examination stage in solving problems and only carried out generalization activities in algebraic thinking. Quitter students do not perform the steps in solving problems and do not fulfill all the indicators of algebraic thinking.